PERBEDAAN ADESI BAKTERI YANG DIISOLASI DARI SUSU KAMBING PERANAKAN ETTAWAH (PE) PADA SEL EPITEL AMBING TIKUS SECARA IN VITRO - , IGNATIUS HARLY P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Goatâs milk is an alternative way to fulfill human nutritional requirement, because they have good savor for the body. One of the obstacle in the dairy goat livestock is the occurance of mastitis disease. Mastitis can caused by some of bacterias, likes group of Staphylococcus, Escherichia, Citrobacter and Klebsiella. Adhesion is important step in the mechanism of bacterial infection. The goal of this research is understanding the differences of adhesion between S. aureus, S. intermedius, S. hyicus, S. epidermidis, C. freundii, E. coli, and K. pneumonia in ratâs mammary epithelial cells using in vitro method. This study is used 7 isolates consist each one isolate of S. aureus, S. intermedius, S. hyicus, S. epidermidis, C. freundi, E. coli, and K. pneumonia which is isolated from Ettawah Crossbreedâs milk. These 7 isolates were reidentification on blood agar plate (PAD) and Gram staining and then tested by catalase test, coagulase test, mannitol fermentation test with mannitol salt agar (MSA), Vogel Johnson agar (VJA), and Voges Proskauer test for Staphylococcy. Citrobacter freundi, E. coli, and K. pneumonia were tested again in McConkey agar (MCA), eosin methylene blue (EMB), indol, methyl red, VP, citrate (IMViC), triple sugar iron (TSI), urea agar, and sugar broth. Adhesion ability of bacterial suspension is conducted by labeling bacteria with Fluorescence Isothicyanate (FITC), then adhesive with ratâs udder epithelial cells. This research result that there is differences between S. aureus, S.intermedius, S. hyicus, S. epidermidis, C. freundii, E. coli, and K. pneumonia. The highest ability of adhesion indicated by S. epidermidis, S. hyicus, S. intermedius, S. aureus, C. freundi, E. coli, and K. pneumonia.